Enhanced solar light driven hydrogen generation and environment remediation through Nd incorporated ZnIn2S4. (December 2020) - Janani, R.; Priyanga, G.Sudha; Behara, Santosh; Melvin, Ambrose Ashwin; Shaheer, A.R.M.; Thomas, Tiju; Neppolian, Bernaurdshaw; Singh, Shubra
Abstract: Visible-light-driven hydrogen production is a promising pathway to realize efficient solar energy utilization. Here, Nd 3+ incorporated ZnIn2 S4 (Nd-ZIS) was synthesized via facile one step hydrothermal method. Raman spectroscopy and X-ray Photoelectron Spectroscopy (XPS) confirm the successful incorporation of Nd 3+ in ZnIn2 S4 . Optical studies reveal the reduction of effective bandgap from 2.7 eV to 2.54 eV upon incorporation of Nd 3+ with improved charge carrier life time of 3.12 ns. Electronic properties of ZIS and Nd-ZIS were investigated from first principle calculations. An attempt to improve photocatalytic activity of ZIS by modification with Nd 3+ ions resulted in degradation of organic pollutant up to 98% under natural sunlight and decrease in life time of trap states up to a nominal value of 200 ms (as evident from photoelectrochemical measurements). The mechanism behind enhancement of photocatalytic activity of ZIS post Nd 3+ integration has been proposed. Nd-ZIS was also utilized for water splitting activity exhibiting a considerable H2 generation ∼3415 μmol g −1 . To the best of our knowledge, activity of Nd 3+ incorporated ZIS has been explored for the first time in present work. It is believed that an in-depth understanding of photoactivity of ZIS would be significantly important for designing materials with desired photocatalytic performance in future. Graphical abstract: Image 1 Highlights: Self-assembled hierarchical structures with improved photocatalytic activity. Introduction of Nd 3+ levels below the conduction band boosts carrier separation. Multifunctional material with superior photoresponse.